2018
DOI: 10.1371/journal.pmed.1002512
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexually transmitted infections among young people in South Africa: A nested survey in a health and demographic surveillance site

Abstract: BackgroundSexually transmitted infections (STIs) and bacterial vaginosis (BV) are associated with increased transmission of HIV, and poor reproductive and sexual health. The burden of STIs/BV among young people is unknown in many high HIV prevalence settings. We conducted an acceptability, feasibility, and prevalence study of home-based sampling for STIs/BV among young men and women aged 15–24 years old in a health and demographic surveillance site (HDSS) in rural KwaZulu-Natal, South Africa.Methods and findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
179
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(232 citation statements)
references
References 39 publications
21
179
2
3
Order By: Relevance
“…In our cohort of HIV uninfected pregnant women, none of the behavioural characteristics iterated in the above studies were associated with BV. The high BV prevalence in the 19-to 24-year-old pregnant women is consistent with a South African rural community survey of nonpregnant women but the BV prevalence in the younger nonpregnant women was higher (41.1%) than that reported for our periurban pregnant population in the same age group (32.8%) [24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our cohort of HIV uninfected pregnant women, none of the behavioural characteristics iterated in the above studies were associated with BV. The high BV prevalence in the 19-to 24-year-old pregnant women is consistent with a South African rural community survey of nonpregnant women but the BV prevalence in the younger nonpregnant women was higher (41.1%) than that reported for our periurban pregnant population in the same age group (32.8%) [24].…”
Section: Discussionsupporting
confidence: 90%
“…The high prevalence of BV (37.3%; 95%CI 33.9-40.9) in this HIV uninfected pregnant population in South Africa is consistent with other sub-Saharan African pregnant populations (Zimbabwe 32.6%, Zambia 48.3%) [20,21] and other South African studies of nonpregnant women at risk for HIV acquisition [22][23][24]. Our study is the first large cohort study of 750 HIV uninfected pregnant women of all ages attending primary health care clinics in a high HIV burden subdistrict of KwaZulu-Natal.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we found that the prevalence of STIs among youths was high, with the highest prevalence found among youths 20-24 years old. This is consistent with several studies (21)(22)(23)(24)(25) showing that the prevalence of STIs was higher among young people aged 20-24 years compared to those 15-19 years. Surprisingly, the prevalence of STIs in 2011 is strikingly higher than in other years.…”
Section: Discussionsupporting
confidence: 93%
“…The risk of acquiring HIV also increases in the presence of sexually transmitted infections (STIs), with the majority of STIs occurring in young people under 25 years of age [8][9][10]. The estimated prevalence of STIs in South Africa among female clinic or community populations aged 15 to 24 years old was 20.6% for chlamydia, 8.9% for gonorrhoea, 20.0% for trichomoniasis, 53.7% for HSV-2, and 52.4% for bacterial vaginosis [11].…”
Section: Introductionmentioning
confidence: 99%